Emojis as an advertising tool for brand positioning - Martinez-Chavez, Clara Fransheska (2024)
This study analyzes the perceptions of young people between the ages of 20 and 26 on the use of emojis as an advertising language tool for the positioning of the “Interbank, eres tú” campaign. It seeks to describe the changes generated in the advertising language and identify how the use of emojis is related to brand positioning. The methodology used is under an interpretative paradigm with a qualitative approach and an ethnographic design. Semi-structured interviews were conducted with 20 young users of Interbank mobile banking. The findings identified are to build a brand image, delimit the target audience and reinforce attributes and benefits related to its products and services. It is recommended to continue the research with some questions that arose from this study, such as whether emojis could completely replace the use of images in advertising and whether emojis can generate a change in brand perception.